1981
DOI: 10.1021/jo00323a030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carbon-13 nuclear magnetic resonance shifts in terms of substituent parameters: statistical comparison of dual and single substituent parameter treatments

Abstract: A systematic comparison is made, by using six different scales of substituent parameters, of the -, ß-, and -carbon-13 chemical shifts for the olefinic moiety in four series of styrene derivatives. There is no systematic significant superiority, in general, of a dual substituent parameter (DSP) treatment with respect to the simpler single substituent parameter (MSP) treatment. In the case of the 7-carbons, with the former type of analysis, the inductive effect is found to be more sensitive than the resonance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In other studies25 we have measured extensive series of 13C spectra for structurally related compounds and found that when the data are measured with precision, at low concentration, the DSP correlations for the Cposition of a conjugating side chain are of good quality and consistently show a negative polar substituent effect. We note that 13C spectra for substituted benzylidene malononitriles have been measured by three groups (Laszlo et al, 33 Posner and Hall,7 and Robinson et al49) and that the SCS values derived differ somewhat. We have therefore carefully remeasured 13C SCS values for a series of these compounds.…”
Section: T H I S C O N T E N T Imentioning
confidence: 78%
“…In other studies25 we have measured extensive series of 13C spectra for structurally related compounds and found that when the data are measured with precision, at low concentration, the DSP correlations for the Cposition of a conjugating side chain are of good quality and consistently show a negative polar substituent effect. We note that 13C spectra for substituted benzylidene malononitriles have been measured by three groups (Laszlo et al, 33 Posner and Hall,7 and Robinson et al49) and that the SCS values derived differ somewhat. We have therefore carefully remeasured 13C SCS values for a series of these compounds.…”
Section: T H I S C O N T E N T Imentioning
confidence: 78%
“…The results of the NMR interpretations of these Knoevenagel products give students a good insight into the charge distributions in the ethylene side chain (6,7). This information may be used to predict the course of conjugate addition reactions and the rate these compounds may exhibit as dienophiles in Diels-Alder reactions.…”
Section: T H Imentioning
confidence: 99%
“…A chiral ligand 3 was synthesized according to a reported procedure 1) . The title compound (128.6 mg, 0.234 mmol) was obtained as a white foam in 68% yield from 98.5 mg (0.344 mmol) of BINOL and 47.2 mg (0.344 mmol) of (R,R)-Bis-(1-cyclohexyl-ethyl)-amine 2) ; [α] All the substrates except for 1i have been reported in literature (1a, c, d, f, k 3) , 1b, l 4) , 1e, h 5) , 1g 6) , 1j 7) ).…”
Section: -Yl)-amine (3)mentioning
confidence: 99%